Helping children and young people to appraise risk in difficult times. (2nd December 2021) - Thornton, Stephanie
Abstract : Anxiety and depression have been on the rise in recent years and it is important to support children and young people to cope with the substantial challenges that have arisen from the current pandemic and climate change.